Aberrant AICA Injury During Translabyrinthine Approach. Issue 10 (December 2020) - Bauer, Ashley M.; Angster, Kristen; Schuman, Ari D.; Thompson, Byron Gregory; Telian, Steven A.
Abstract : Objective: To define a complication of the translabyrinthine surgical approach to the posterior fossa related to a rare variant of the anterior inferior cerebellar artery (AICA) that penetrated into the petrous temporal bone. Patient: A healthy 59-year-old male with a unilateral sporadic vestibular schwannoma. Intervention: The patient elected to undergo a translabyrinthine approach for resection of a vestibular schwannoma. An aberrant loop of AICA was encountered during the temporal bone dissection within the petrous portion of the temporal bone. Outcomes: The patient suffered a presumed ischemic insult resulting in a fluctuating ipsilateral facial paresis and atypical postoperative nystagmus. Results: MRI demonstrated an ischemic lesion in the vascular distribution of the right anterior-inferior cerebellar artery, including the lateral portion of the right cerebellar hemisphere, middle cerebellar peduncle, and bordering the right cranial nerve VII nucleus. His functional recovery was excellent, essentially identical to the anticipated course in an otherwise uncomplicated surgery. Conclusions: This case highlights the irregular anatomy of the AICA as well as the importance of thorough neurological exams in the postsurgical lateral skull base patient.